Ruptured arteriovenous fistula pseudoaneurysm treatment by balloon‐assisted direct percutaneous thrombin injection. Issue 2 (22nd November 2021) - Loureiro, Luís; Mendes, Daniel; Sousa, Clemente Neves; Almeida, Paulo; Norton de Matos, António; Teles, Paulo; Rego, Duarte; Teixeira, Gabriela; Teixeira, Sérgio; Antunes, Inês; Costa, Luísa Lemos
Abstract: We present the case of a male patient on hemodialysis with a ruptured pseudoaneurysm in a brachiocephalic arteriovenous fistula (AVF) and with edema and pain in the right arm attended to in the emergency department. An ultrasonographic scan identified a ruptured pseudoaneurysm with hemorrhagic infiltration of the arm muscular tissues. We performed a percutaneous ultrasound‐guided thrombin injection with an angioplasty balloon inflated in the lumen of the AVF achieving the pseudoaneurysm thrombosis. After 6 months of follow‐up, the patient's arteriovenous access remains functional. Percutaneous ultrasound‐guided thrombin injection assisted by an angioplasty balloon may be a good alternative to surgical intervention in the treatment of symptomatic growing pseudoaneurysms of the arteriovenous fistula with the benefit of preserving the vascular access.